Lagrangian temperature and vertical velocity fluctuations due to gravity waves in the lower stratosphere - Podglajen, Aurélien; Hertzog, Albert; Plougonven, Riwal; Legras, Bernard (Geophysical Research Letters, 2016)
International audience Wave-induced Lagrangian fluctuations of temperature and vertical velocity in the lower stratosphere are quantified using measurements from superpressure balloons (SPBs). Observations recorded every minute along SPB flights allow the whole gravity wave spectrum to be described and provide unprecedented information on both the intrinsic frequency spectrum and the probability distribution function of wave fluctuations. The data set has been collected during two campaigns coordinated by the French Space Agency in 2010, involving 19 balloons over Antarctica and 3 in the deep tropics. In both regions, the vertical velocity distributions depart significantly from a Gaussian behavior. Knowledge on such wave fluctuations is essential for modeling microphysical processes along Lagrangian trajectories. We propose a new simple parameterization that reproduces both the non-Gaussian distribution of vertical velocities (or heating/cooling rates) and their observed intrinsic frequency spectrum.